Usage of solar energy and its status in Malaysia - Islam, M.R.; Saidur, Rahman; Rahim, N.A.; Solangi, K.H. (Engineering e-Transaction, 2010)
Solar energy is radiant energy that is produced by the sun and every day sun radiates, or sends out an enormous amount of energy. The sun radiates more energy in one second then people have used since beginning of time. There are lot of technology are used now a days to harness the energy from the sun as solar thermal energy, ocean thermal energy conversion, solar ponds, solar tower and photovoltaic systems. Green campaign is one of the hot topics among the Malaysian. The main objective of green campaign is to create awareness among the public to protect our environment. In Malaysia there are a lot of organization organizing green campaign such as Environmental Protection Society Malaysia (EPSM), Malaysia Environment NGOs (MENGO) and Treat Every Environment Special Sdn. Bhd. (TRESS). Price of solar energy is very reasonable and very depending upon the amount of energy you need and the size of the panels required. The payback time for solar water heating now makes solar energy financially viable for the majority of domestic applications.